The linkages between land use change, land degradation and biodiversity across East Africa - Maitima, J.M.; Mugatha, Simon M.; Reid, Robin S.; Gachimbi, L.N.; Majule, A.E.; Lyaruu, H.; Pomery, D.; Mugisha, S.; Mathai, S. (2009)
Land use changes in East Africa have transformed land cover to farmlands, grazing lands, human settlements and urban centers at the expense of natural vegetation. These changes are associated with deforestation, biodiversity loss and land degradation. A synthesis of results of long term research by an interdisciplinary team reveals the linkages between land use change, biodiversity loss and land degradation. The results indicate that as native vegetation is lost, indigenous plant and animal biodiversity and plant cover are lost. Pastoralism maintains native plant and animal species more effectively than crop cultivation. As croplands expand, soil fertility and moisture drops and soils erode more easily. Farmers who grow many crops conserve native plant species better than those who grow only one crop. Increased crop diversity encourages regeneration of indigenous plant species. Moderate farming as in the less intensive low input rainfed mixed crop farming, in less forested areas increases tree cover thus increasing the biodiversity. Farmers’ who combine livestock rearing with cropping, use livestock manure to replenish soil nutrients in their farms and are thus able to maintain higher productivity. Farming in grasslands, woodlands and bushland areas where there are fewer trees, increases the diversity of habitats due to introduction of agrosystems that attract new species of birds. However, if the farming is intensified and the diversity of habitats is reduced biodiversity is also reduced. This paper presents findings of the investigations on these linkages in a diverse farming and herding systems ranging from lowlands to high mountains land uses.